ARE THERE OBLIGATIONS WITHOUT RIGHTS? - Heller, Agnes (Revista da Faculdade de Direito UFPR, 2010)
In all command-obedience relations of asymmetric reciprocity, obligations or rather duties do not go normally with corresponding rights. There are no rights related to such relationships, at least not in the present understanding of the word “right”, since they are prerogatives. But there are obligations based on morals, if not on rights, also in relations of asymmetric reciprocity. Only in a relation of symmetric reciprocity do rights appear as foundations (archai) for claims, both in a positive, and in a negative sense. We have obligations to future generations, even responsibilities for living up to those obligations, but future generations cannot have rights. There is not, and cannot be, symmetric reciprocity between us and any future generation, in fact no reciprocity at all; there are obligations without corresponding rights.The cases of prospective responsibility, of being in charge, also implies obligations irrespective of the circumstance whether the parties towards whom we have obligations are the bearers of rights or not. Intergenerational justice does not presuppose extant rights whereas potential rights are just projections or metaphors with little relevance, for they are not binding.